Correlation between computed tomography findings and liver function parameters in chronic liver disease - Moeen ud din Khan Khalil; Syed Kazim Shah Bukhari; Syed Murtaza Shah Bukhari; Mian Zia Shah; Mian Raza Shah (Journal of Shalamar Medical & Dental College, 2025)
Background: Chronic liver disease (CLD) leads to cirrhosis, hepatocellular carcinoma (HCC), and liver failure. Non-invasive assessment tools are crucial for the early detection and management of these complications of CLD.